2004
DOI: 10.1111/j.1460-9592.2004.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous ketorolac in the neonate and premature babies

Abstract: Ketorolac could represent an efficacious analgesic alternative to opioids, particularly in neonates. It would avoid the side-effects associated with opioid analgesics, especially respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The Food and Drug Administration has approved ketorolac for use in children older than 2 years, and data describing its safe use in infants older than 6 months have also been described [1,4,7]. Papacci et al [8] previously reported 18 neonates to whom ketorolac was administered in a postoperative or postprocedural setting. They concluded ketorolac to be safe and efficacious in this age group.…”
Section: Discussionmentioning
confidence: 92%
“…The Food and Drug Administration has approved ketorolac for use in children older than 2 years, and data describing its safe use in infants older than 6 months have also been described [1,4,7]. Papacci et al [8] previously reported 18 neonates to whom ketorolac was administered in a postoperative or postprocedural setting. They concluded ketorolac to be safe and efficacious in this age group.…”
Section: Discussionmentioning
confidence: 92%
“…Most children required remedication for pain within 4 h; 58% for ketorolac and 63% for morphine. Papacci et al (19) reported significant analgesic efficacy within 0.5 h and up to 6 h after dose in an observational unblinded study of 18 neonates and premature babies given 1 mg/kg IV ketorolac for postoperative or procedure-related pain.…”
Section: Discussionmentioning
confidence: 97%
“…The primary strategy for treatment of pain in postoperative cardiac patients is the administration of opioids. However, after cardiac surgery, infants may be physiologically and anatomically predisposed to respiratory depression with administration of opioids (6). Therefore, maintaining analgesia while minimizing adverse effects in very young postoperative patients is a challenge.…”
Section: Commentsmentioning
confidence: 99%